The daily routine of management in Primary Health Care: perceptions of managers (Research, Society and Development, 2022)
Objective: To investigate the perception of management in Family Health Units, from the managers' perspective. Methods: exploratory study, using a qualitative approach. Six managers of the aforementioned Units in a municipality in Minas Gerais participated. For data collection, semi-structured, audio-recorded interviews were used, from October to November 2017, taking into account the research question: What do the managers of the Family Health Units think, and how do they perceive management in that circumstance? Data verification followed the Content Analysis, thematic modality, and was guided by the precepts of the work process and co-management in health. Results: the following thematic categories emerged: Manager attribution in the daily life of PHC; Shared management; and Challenges and Progress for PHC management. The thematic categories showed elements of the daily work of managers in health units, as well as the challenges and advances in this scenario. Final Considerations: The importance of shared management is highlighted, with emphasis on the collaboration of nurses from the Family Health Strategy, the support and communication of the Municipal Health Department, and specialization as tools that can contribute to the qualification of the management process.